Financial Report Analysis in Measuring the Financial Performance of State-Owned Banks - Nyoman Jatiningsih; Ni Nyoman Suli Asmara Yanti (Transpublika Publisher, 2026)
This research is motivated by the dynamics of the financial performance of the State-Owned Enterprise (SOE) banking industry during the 2020-2024 period, which was influenced by the COVID-19 pandemic and the economic recovery process. Differences in performance achievements between banks indicate the need for a comprehensive assessment of the financial health of SOE banks. The main objective of this study is to analyze the financial performance of SOE banks in terms of solvency, profitability, and operational efficiency. The study used a descriptive quantitative design with a purposive sampling technique, utilizing secondary data in the form of the annual financial reports of four SOE banks listed on the Indonesia Stock Exchange. Financial performance was measured using the Debt to Asset Ratio to assess solvency, Return on Assets and Net Interest Margin to assess profitability, and the Operating Cost to Operating Income ratio to assess operational efficiency. The results show that the financial condition of SOE banks is in the healthy to very healthy category. Bank Rakyat Indonesia and Bank Mandiri recorded the most optimal performance, especially in the aspects of profitability and efficiency, while Bank Negara Indonesia is in the good category with a consistent improvement trend. However, Bank Tabungan Negara still faces challenges, especially related to low levels of profitability and operational efficiency. This study concludes that increasing operational efficiency and optimizing the utilization of productive assets are important implications for strengthening competitiveness and maintaining the sustainability of the financial performance of state-owned banks.